Perancangan Sistem Informasi Transaksi Keuangan Cum Talenta GKPS - Rella Robet Saragi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Cum Talenta GKPS is one of the business entities engaged in the field of savings and loans, which serves members especially in the field of savings and loans. Where data processing still uses conventional methods, so that members who will make savings and loan transactions need quite a long time in serving members. With this, it is expected to help cooperatives to improve their member services and to store data or other important documents that must be stored properly so that the presentation of information is relatively fast and accurate. To overcome this problem, several studies were conducted such as interview methods and observations. For system modeling, the author uses a structured design method with design tools, namely flow maps, context diagrams, data flow diagrams and DFDs. Implementation and creation of the system using the Visual Basic programming language and MySQL database. The financial information system designed aims to build a computerized information system so that it is easier for farmer group members to process member data, transaction data, savings data and member loan data.